WATER COLUMN FEATURES AND SEAFLOOR CHARACTERISTICS USING SIMULTANEOUS MULTIBEAM WATER COLUMN DETECTION - Aziz, K.N.A.; Mahmud, M.R.; Hasan, R.C.; Gunathilaka, M.D.E.K; Peter, B.N.; Tajam, J.; Roslani, M.A.; Kamaruddin, S.A. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Simultaneous mid-water and seafloor classification enables the study of the relationship between seafloor characteristics and water column features known as habitat interactions. Normally, the focus of these data is only on one part of either the water column or the seafloor. This water column data is usually filtered out to form an accurate bathymetric surface. Otherwise, this will cause data duplication or loss and degrade the accuracy of the data. This study aimed to produce a comprehensive map using a Multibeam Echosounder System (MBES). The data acquisition was carried out using WASSP WMB-160f MBES and a camera recorder was used for verification. Data comparison was carried out through bathymetric and backscatter analysis and filtered at the minimum threshold. The result showed that both data were able to be detected simultaneously at a comparable and effective result without neglecting any details behind. The water column data was at good resolution for detection below the 300 kHz, although the data obtained from this study did not show the real shape and size of the detected object. In addition, the seafloor could also be well detected and properly classified according to survey requirements.